Ptosis and diplopia—sole manifestations in multiple myeloma - Nambiar, Rakul K.; Nair, Sreejith G.; Mathew, Sherin P.; Manohar, Anoop T. (Annals of Blood, 2017)
Multiple myeloma, a plasma cell neoplasm commonly targets bone, bone marrow, and the kidneys. Extramedullary plasmacytomas, even in advanced disease only rarely present with diplopia and ptosis, which result from mechanical interference of the orbital muscles by the tumour. We report a case of advanced myeloma, whose sole presentation was diplopia and ptosis. A 63-year-old-woman, with no significant ophthalmic history presented with drooping of her right eyelid and diplopia of 4 months duration. MRI of the brain demonstrated multiple calvarial lesions. The largest lesion was seen in the right frontal bone whose intraorbital component was compressing the superior rectus, levator superioris and indenting the superior margin of the globe. Bone marrow aspiration revealed plasmacytosis. Patient was diagnosed to have IgA Kappa multiple myeloma.